Evaluation of adaptation of pharmaceutical forms in a pediatric hospital from Manaus - ELIANE PIMENTEL NÓBREGA; SUELY OLIVEIRA CHAGAS; IGOR RAFAEL DOS SANTOS MAGALHÃES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
Background: The pharmaceutical form adaptation of medicines for pediatric use is frequent in Brazilian hospitals due to the lack of suitable formulations for children. This practice has been defined as an unlicensed use. Objective: In the present study, a descriptive, quantitative and retrospective study covering different aspects related to pharmaceutical adaptation was carried out in a pediatric hospital in Manaus during the year of 2016. Methods: Through the data collection from the hospital records, the different pharmacological classes and pharmaceutical forms used and produced, some aspects of good handling practices and the standard operating procedures applied in these formulations were evaluated. In addition, the consultation of the availability of ready-made formulations in the national market as alternatives to the hospital's production process and the accomplishment of calculations to verify the price comparison were carried out. Results: In this study, diuretics were the most modified medicines (15,4%). The most produced therapeutic agents were Potassium Chloride and the association Spironolactone and Hydrochlorothiazide (21.2%). The ready liquid dosage forms of dexamethasone, potassium chloride, oseltamivir and midazolam were found in the search on the market. In addition, it has been found that, in the comparison between the production process and the market purchase, the adaptation is financially advantageous, according to the calculations made. Conclusions: Therefore, it is concluded that the adaptation of pharmaceutical forms is a reality in the studied hospital and the need to purchase the industrialized product or to adapt the pharmaceutical form must take into account not only the financial aspect but also other aspects such as demand, availability in the Market, pharmacotechnical aspects, safety, effectiveness, among other points.